The Effect Of A Realistic Mathematics Approach On Students' Mathematical Critical Thinking Ability - Nasution, Layla Rizqi Isnaini Fadhilah; Neliwati; Andhany, Ella (Yana Research, 2022)
This study aims to determine the effect of a realistic mathematical approach on students’ mathematical critical thinking skills in the flat-sided geometry material at SMP Negeri 1 Stabat. This reasearch is a quantitative reasearch, with the type of experimental research. The population is all class VIII students, totaling 118 people. The sample used by the reasercher is class VIII-1 and class VIII-2 with 30 students each to serve as an experimental class determined by purposive sampling technique. Data collection techniques by giving pre-test and post-test to determine students’ ability to think critically mathematically. The data analysis technique in this reaserch is using hypothesis testing. Reseach hypothesis testing using t test. Based on the results of the research and hypothesis testing, the researcher can conclude as follows: (1) There is a significant effect on the t test, namely t count > t table with t count = (7.330) and t table = (1.669). it can be concluded that there is a significant effect of the realistics mathematics approach on students’ mathematical critical thinking skills in the flat-sided geometry material at SMP Negeri 1 Stabat.